Interface reinforced cubic engineered aggregate metamaterial concrete and preparation method thereof
Patent Information
- Application Number
- CN202611143253.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-23
AI Technical Summary
现有技术虽然提供了方形工程骨料超材料混凝土的构想,但其关注点在于骨料本身的构成与整体配合比,对于因软涂层引入而导致的界面粘结问题,并未给出任何有效的解决方案
1)界面粘结性能增强:通过对立方体工程骨料的软质涂层进行碱性溶液化学预处理产生微观蚀刻,增加表面粗糙度,同时可能引入活性极性基团,从物理咬合与化学粘结双重机制上增强骨料与水泥砂浆基体的界面粘结力,解决因软涂层引入而导致的界面薄弱难题。
Smart Images

Figure CN122958091A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of civil engineering materials technology, and in particular to an interface-reinforced cubic engineering aggregate metamaterial concrete and its preparation method. Background Technology
[0002] Metamaterial design based on phonon crystals and local resonance principles provides a theoretical foundation for developing metamaterial concrete with wave-controlled properties. These materials, by introducing periodically or randomly distributed engineering aggregates with specific core-shell structures into a traditional concrete matrix, can generate band gaps within a specific frequency range, thereby effectively attenuating elastic waves such as explosive shock waves and seismic stress waves. This demonstrates broad application prospects in fields such as military protection and seismic isolation of important buildings.
[0003] Cubic engineering aggregates, as a typical type of localized resonant unit, are usually composed of a high-density, high-modulus rigid core material and an outer low-modulus soft coating. However, this very soft coating, essential for achieving wave regulation, suffers from a significant difference in chemical properties and surface energy compared to inorganic hydrated calcium silicate gel. This difference leads to the weakest link in the entire composite material system: the interfacial bond between the coating and the cement mortar matrix. This weak interface not only becomes a source of stress concentration but also severely restricts the overall structural strength and load-bearing capacity of metamaterial concrete, greatly limiting its widespread application in practical engineering.
[0004] Currently, research on improving the mechanical properties of metamaterial concrete mainly focuses on optimizing the mix proportion of the mortar matrix or adding macroscopic reinforcement methods such as fibers. Although existing technologies have provided the concept of metamaterial concrete with square engineering aggregates, their focus is on the composition of the aggregate itself and the overall mix proportion. They have not provided any effective solutions for the interfacial bonding problem caused by the introduction of soft coatings. Summary of the Invention
[0005] The purpose of this invention is to provide an interface-strengthened cubic engineering aggregate metamaterial concrete and its preparation method. By performing a simple and controllable interface chemical pretreatment on the soft coating of the cubic engineering aggregate, the interfacial adhesion between the aggregate and the mortar matrix is enhanced, thereby improving the mechanical properties of the metamaterial concrete while maintaining its excellent fluctuation control function.
[0006] To achieve the above objectives, the present invention provides an interface-reinforced cubic engineering aggregate metamaterial concrete, comprising a cement mortar matrix and cubic engineering aggregate uniformly dispersed in the matrix; The cubic engineering aggregate consists of a rigid core and a soft coating covering the outside of the rigid core. The surface of the soft coating is chemically pretreated with an alkaline solution to form a modified interface layer. The modified interface layer is used to enhance the interfacial adhesion between the cubic engineering aggregate and the cement mortar matrix.
[0007] Preferably, the alkaline solution is an aqueous sodium hydroxide solution with a molar concentration of 0.2 mol / L to 1.0 mol / L.
[0008] Preferably, the molar concentration of the sodium hydroxide aqueous solution is 0.5 mol / L to 1.0 mol / L.
[0009] Preferably, the volumetric content of the cubic engineering aggregate in the metamaterial concrete is 5%-15% of the total volume of the metamaterial concrete.
[0010] Preferably, the rigid core material is a steel core, and the soft coating is a rubber coating.
[0011] This invention also provides a method for preparing the above-mentioned metamaterial concrete, comprising the following steps: S1. Pretreatment of cubic engineering aggregate: Immerse the cubic engineering aggregate in an alkaline solution, soak it at room temperature for 3 hours, then take it out and dry it to obtain cubic engineering aggregate with chemically modified surface. S2. Mixing and stirring: Cement, fine aggregate, coarse aggregate, water and admixtures are put into a mixer and stirred to make cement mortar; then the cubic engineering aggregate treated in S1 is added to the cement mortar and stirred until it is evenly dispersed to obtain the metamaterial concrete mixture. S3. Casting and Curing: The supermaterial concrete mixture is poured into the mold, vibrated to compact it, and then cured.
[0012] Preferably, in S2, the mixing is carried out using a vibrating mixer, with a dry mixing time of 5 minutes and a wet mixing time of 10 minutes.
[0013] Preferably, in S3, the curing is standard curing room curing to the specified age, curing temperature is 20±2℃, and curing humidity is not less than 95%.
[0014] Therefore, the present invention employs the above-mentioned interface-reinforced cubic engineering aggregate metamaterial concrete and its preparation method, which has the following beneficial effects: 1) Enhanced interfacial bonding performance: By performing alkaline solution chemical pretreatment on the soft coating of cubic engineering aggregate to produce micro-etching, the surface roughness is increased. At the same time, active polar groups may be introduced, which enhances the interfacial bonding force between aggregate and cement mortar matrix from the dual mechanism of physical interlocking and chemical bonding, solving the problem of weak interface caused by the introduction of soft coating.
[0015] 2) Improved mechanical properties: The method is simple and controllable, with significant enhancement effects, improving the compressive strength and elastic modulus of metamaterial concrete, transforming metamaterial concrete from a single-function material into a structure-function integrated material, meeting the dual requirements of protective engineering for load-bearing capacity and fluctuation control.
[0016] 3) The wave regulation function remains intact: the chemical modification only acts on the surface interface area of the aggregate, and has no effect on the geometric size, core-shell structure and local resonance effect of the cubic engineering aggregate itself, ensuring that the core wave attenuation function of metamaterial concrete is completely preserved.
[0017] 4) Simple process, low cost and good compatibility: Interface modification can be completed by room temperature soaking treatment, which is easy to scale up production and is compatible with existing concrete preparation processes, and has engineering application prospects.
[0018] 5) Performance can be flexibly adjusted: By adjusting the concentration of alkaline solution and the amount of cubic engineering aggregate, the mechanical properties and workability can be flexibly adjusted to meet the differentiated needs of different engineering scenarios.
[0019] 6) Clear microscopic mechanism: Through systematic microscopic morphology observation, a complete chain of evidence is provided for the interface modification effect, proving the scientific nature and innovation of the technical solution.
[0020] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0021] Figure 1 These are schematic diagrams of the cubic engineering aggregate structure and modification types of the present invention; Figure 2 This is a dual Y-axis graph comparing the static uniaxial compressive strength and elastic modulus of metamaterial concrete with different degrees of chemical modification of CEA by NaOH solution. Figure 3 This is a dual Y-axis graph comparing the static uniaxial compressive strength and elastic modulus of metamaterial concrete with different CEA volume contents. Figure 4 These are SEM microstructure comparison images of four types of cubic engineering aggregates. Detailed Implementation
[0022] The technical solutions of the present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0023] Raw materials and preparation of cubic engineering aggregates: The main raw materials used in the embodiments of this invention are as follows: 1. Cementitious material: PO 52.5 grade ordinary Portland cement is used.
[0024] 2. Aggregates: Fine aggregate is natural river sand; coarse aggregate is ordinary crushed stone.
[0025] 3. Cubic Engineering Aggregate (CEA): CEA has a side length of 20mm and consists of a rigid steel core and a soft rubber coating. The steel core is a cube with a side length of 16mm and a density of 7800kg / m³. 3 The yield strength is 235 MPa, and the elastic modulus is 210 GPa. The rubber coating thickness is 2 mm, and the density is 1250 kg / m³. 3 The tensile strength is 13.5 MPa and the elastic modulus is 4.2 MPa.
[0026] 4. Modified solutions: Analytical grade sodium hydroxide was prepared into aqueous solutions with different molar concentrations.
[0027] Pretreatment of cubic engineering aggregates: such as Figure 1 As shown, four types of CEA were prepared for use in metamaterial concrete, including unmodified CEA (denoted as CEA1) and three types of CEA chemically modified with NaOH solutions of different concentrations. The modification process was as follows: CEA was immersed in NaOH solutions with molar concentrations of 0.2 mol / L, 0.5 mol / L, and 1.0 mol / L, respectively, and treated at room temperature for 3 hours before being removed and dried, and then denoted as CEA2, CEA3, and CEA4, respectively.
[0028] Mix design: This invention designs seven mix proportion groups, including metamaterial concrete specimens containing different types of CEA and different volumetric admixtures, as well as ordinary concrete specimens as a performance comparison benchmark. Detailed mix proportions for the concrete specimens used in the quasi-static test are shown in Table 1. Each metamaterial concrete specimen is uniquely identified using the format "Concrete Type-CEA Type-CEA Volumetric Content". For example, MC-CEA1-V10 represents a metamaterial concrete specimen containing 10% CEA1 by volumetric admixture.
[0029] Table 1. Mix proportions of metamaterial concrete and ordinary concrete specimens
[0030] Example 1: Preparation and properties of benchmark ordinary concrete.
[0031] Weigh all raw materials according to the proportions in Table 1 for ordinary concrete. Using a forced mixer, first dry mix the cement, river sand, and crushed stone for 5 minutes until homogeneous, then add water and continue wet mixing for 10 minutes to form a homogeneous concrete mixture. The slump was tested according to the "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016), and found to be 492.50 mm. The mixture was cast into cylindrical specimens of Φ100 mm × 200 mm and compacted on a vibrating table. The specimens were demolded 24 hours after molding and placed in a standard curing room (20±2℃, humidity ≥95%) for 28 days. A static uniaxial compression test was conducted according to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T 50081-2019), and the 28-day compressive strength was measured to be 52.51 MPa, and the elastic modulus was 27.32 GPa.
[0032] Example 2: Preparation and properties of metamaterial concrete containing unmodified CEA (MC-CEA1-V10).
[0033] Weigh the raw materials according to the proportions of MC-CEA1-V10 group in Table 1. The mixing process is the same as in Example 1. First, dry mix cement, river sand, and crushed stone for 5 minutes until uniform, then add water and wet mix for 10 minutes to make cement mortar. Then add unmodified CEA1 and continue mixing until uniformly dispersed. Due to the addition of CEA, the slump of the fresh concrete was measured to be 439.00 mm. The molding and curing process is the same as in Example 1. The 28-day compressive strength was measured to be 27.44 MPa, and the elastic modulus was 15.67 GPa. Compared with the benchmark ordinary concrete, the mechanical properties decreased significantly due to the weak bond between CEA and the matrix interface.
[0034] Example 3: Preparation and properties of metamaterial concrete (MC-CEA2-V10) containing 0.2 mol / L NaOH-modified CEA.
[0035] The difference between this embodiment and Example 2 is that CEA2 treated with 0.2 mol / L NaOH solution was used instead of CEA1. The preparation process is exactly the same. The slump of the fresh concrete was measured to be 443.20 mm. The 28-day compressive strength was 30.02 MPa, and the elastic modulus was 15.79 GPa. Compared with MC-CEA1-V10, the mechanical properties have begun to improve, proving that the interface modification has initially taken effect.
[0036] Example 4: Preparation and properties of metamaterial concrete (MC-CEA3-V10) containing 0.5 mol / L NaOH-modified CEA.
[0037] The difference between this embodiment and Example 2 is that CEA3 treated with 0.5 mol / L NaOH solution was used. The slump of the fresh concrete was measured to be 407.00 mm. The 28-day compressive strength was 32.06 MPa, and the elastic modulus was 15.95 GPa. The mechanical properties continued to improve, indicating that increasing the modifier concentration helps to further enhance interfacial bonding.
[0038] Example 5: Preparation and properties of metamaterial concrete (MC-CEA4-V10) containing 1.0 mol / L NaOH-modified CEA.
[0039] The difference between this embodiment and Example 2 is that CEA4 treated with 1.0 mol / L NaOH solution was used. The slump of the fresh concrete was measured to be 352.50 mm. The 28-day compressive strength reached 36.44 MPa, and the elastic modulus was 16.07 GPa. Compared with the unmodified MC-CEA1-V10, the compressive strength increased by 32.8%, and the elastic modulus was also significantly improved, fully demonstrating the excellent effect of the interfacial chemical modification strategy of this invention.
[0040] Example 6: Preparation and properties of metamaterial concrete (MC-CEA3-V5) containing 5% volumetric modified CEA.
[0041] Weigh the raw materials according to the proportions for the MC-CEA3-V5 group in Table 1. Use CEA3 treated with 0.5 mol / L NaOH solution. The mixing process is the same as in Example 2. The slump of the fresh concrete was measured to be 527.50 mm. The 28-day compressive strength was 47.44 MPa, and the elastic modulus was 22.41 GPa. The results show that a 5% admixture achieves the best balance in terms of uniaxial compressive performance, elastic modulus, and workability.
[0042] Example 7: Preparation and properties of metamaterial concrete (MC-CEA3-V15) containing 15% volumetric modified CEA.
[0043] Weigh the raw materials according to the proportions for MC-CEA3-V15 group in Table 1. Use CEA3 treated with 0.5 mol / L NaOH solution. The mixing process is the same as in Example 2. The slump of the fresh concrete was measured to be 331.30 mm. The 28-day compressive strength was 20.19 MPa, and the elastic modulus was 13.85 GPa.
[0044] The performance of Examples 1-7 was compared and analyzed, and the results are as follows: Figure 2 , Figure 3 And as shown in Table 2.
[0045] Table 2 Summary of the performance of different metamaterial concrete and ordinary concrete specimens
[0046] The following conclusions can be drawn from the data in Table 2: 1) Significant interfacial modification effect: Under the same CEA dosage (10%), the compressive strength and elastic modulus of metamaterial concrete showed a monotonically increasing trend with the increase of NaOH pretreatment concentration. When the concentration reached 1.0 mol / L, the compressive strength increased by 32.8% compared with the unmodified group, proving that the interfacial strengthening effect was extremely significant.
[0047] 2) Workability is controllable: The slump decreases with increasing NaOH concentration, indicating that the modification affects the hydrophilicity of the CEA surface, which provides a basis for workability control during construction.
[0048] 3) Effect of dosage: Within the dosage range of 5% to 10%, the metamaterial concrete using the modified CEA of this invention exhibits better mechanical properties than the unmodified group.
[0049] To delve deeper into the root causes of the performance improvement, scanning electron microscopy (SEM) was performed on the surfaces of four CEA types (CEA1 to CEA4): 1) such as Figure 4 As shown in Figure (a), the surface of the rubber coating in CEA1 is relatively smooth and dense, with only slight textures from the natural manufacturing process. This surface is not conducive to the penetration and anchoring of cement slurry.
[0050] 2) such as Figure 4 As shown in Figure (b), obvious erosion marks begin to appear on the surface of CEA2, the smoothness is destroyed, and a micron-scale uneven structure is produced. The amount of ettringite increases and the roughness increases.
[0051] 3) such as Figure 4 As shown in Figure (c), erosion is intensified in CEA3, and the surface exhibits clear and uniformly distributed grooves and pore structures, forming a more developed micro-rough morphology.
[0052] 4) such as Figure 4 As shown in Figure (d), the surface of CEA4 is significantly eroded, exhibiting maximum roughness and porosity.
[0053] SEM observations confirmed that NaOH solution pretreatment effectively etched the surface of the CEA rubber coating, significantly increasing its roughness and potentially introducing polar groups such as hydroxyl groups. This alteration in microstructure and chemical properties greatly improved its mechanical and chemical adhesion to cement hydration products, thus enhancing interface quality.
[0054] Therefore, the present invention adopts the above-mentioned interface-strengthened cubic engineering aggregate metamaterial concrete and preparation method. By performing simple and controllable interface chemical pretreatment on the soft coating of cubic engineering aggregate, the interfacial adhesion between the aggregate and the mortar matrix is significantly enhanced, thereby greatly improving the mechanical properties while maintaining the excellent fluctuation control function of metamaterial concrete.
[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A type of interface-reinforced cubic engineering aggregate metamaterial concrete, characterized in that, It includes a cement mortar matrix and cubic engineering aggregates uniformly dispersed in the matrix; The cubic engineering aggregate consists of a rigid core and a soft coating covering the outside of the rigid core, and the surface of the soft coating is chemically pretreated with an alkaline solution to form a modified interface layer. The modified interface layer is used to enhance the interfacial bond between the cubic engineering aggregate and the cement mortar matrix.
2. The metamaterial concrete according to claim 1, characterized in that, The alkaline solution is an aqueous solution of sodium hydroxide with a molar concentration of 0.2 mol / L to 1.0 mol / L.
3. The metamaterial concrete according to claim 2, characterized in that, The molar concentration of the sodium hydroxide aqueous solution is 0.5 mol / L to 1.0 mol / L.
4. The metamaterial concrete according to claim 1, characterized in that, The volumetric content of the cubic engineering aggregate in the metamaterial concrete is 5%-15% of the total volume of the metamaterial concrete.
5. The metamaterial concrete according to claim 1, characterized in that, The rigid core material is a steel core, and the soft coating is a rubber coating.
6. A method for preparing metamaterial concrete as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Pretreatment of cubic engineering aggregate: Immerse the cubic engineering aggregate in an alkaline solution, soak it at room temperature for 3 hours, then take it out and dry it to obtain cubic engineering aggregate with chemically modified surface. S2. Mixing and stirring: Cement, fine aggregate, coarse aggregate, water and admixtures are put into a mixer and stirred to make cement mortar; then the cubic engineering aggregate treated in S1 is added to the cement mortar and stirred until it is evenly dispersed to obtain the metamaterial concrete mixture. S3. Casting and Curing: The supermaterial concrete mixture is poured into the mold, vibrated to compact it, and then cured.
7. The method according to claim 6, characterized in that, In S2, the mixing is carried out using a vibrating mixer, with a dry mixing time of 5 minutes and a wet mixing time of 10 minutes.
8. The method according to claim 6, characterized in that, In S3, the curing is standard curing room curing to the specified age, curing temperature is 20±2℃, and curing humidity is not less than 95%.